Nigeria : Experience with Structural Adjustment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
Over the past two decades, Nigeria has not reaped fully the benefits of its national wealth despite its efforts at structural adjustment. This paper concludes that the facts do not justify the negative image that structural adjustment has had in Nigeria. Vigorous market reforms and tight financial policies had resulted in economic growth and employment expansion, but they were abandoned too soon to have sustained benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet